ความไว้วางใจของประชาชนที่มีต่อองค์การบริหารส่วนตำบล: กรณีศึกษาเปรียบเทียบองค์การบริหารส่วนตำบลช่องกับองค์การบริหารส่วนตำบลปลักหนู - จักรพงษ์ หนูดำ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The study presents a mixture of both qualitative and quantitative research findings with the objective of studying a comparison of the level of trust in tambon administration organizations between the Chong Tambon Administration Organization and the Pluknoo Tambon Administration Organization, and to study the factors influencing public trust in the Chong Administration Organization and the Pluknoo Tambon Administration Organization. The researcher is interested in studying tambon administration organizations that have been awarded in comparison to tambon administration organizations that have not been awarded under the award terms of the award for outstanding local governments that were awarded by the Office of the Decentralization to the Local Government Organization Committee (DLOC) for 2011. Furthermore, it is assumed that the Chong Tambon Administration Organization which received the award should have more public trust than the Pluknoo Tambon Administration Organization which was not awarded. The number of subjects in the sample group for the present study was selected by random sampling from the population of all residents living in the Chong Tambon Administration Organization area and the Pluknoo Tambon Administration Organization for a total of 200 subjects for one case study.According to the research findings, the level of public trust in the Chong Tambon Administration Organization was moderate. As for the Pluknoo Tambon Administration Organization, the level of public trust was not very high. The aforementioned findings concur with the research hypothesis that the Chong Tambon Administration Organization had a higher level of public trust than the Pluknoo Tambon Administration Organization. And the factors influencing the level of public trust in the Chong Tambon Administration Organization and the Pluknoo Tambon Administration Organization were different. The differing factors influencing the level of public trust were the factor of transparency in TAO work and the factor of politics in the government system. These findings support the research hypothesis that the factors influencing public trust in tambon administration organizations that received the outstanding tambon administration organization award and those that did not receive the award should be different.